Standardized modulation of the injection site allows for insulin dose reduction without deterioration of metabolic control. (October 2014) - Pfützner, A.; Dissel, S.; Forkel, C.; Grenningloh, M.; Bitton, G.; Nagar, R.; Forst, T.
Abstract Objectives: Use of an injection site modulation device (InsuPad) in intensive insulin treatment reduces frequency of hypoglycemia and prandial insulin requirements by enhancing subcutaneous microcirculation. This meal tolerance test (MTT) investigation was performed as a sub-study during the real-world BARMER study to demonstrate non-inferiority of the reduced insulin doses observed in this study with respect to metabolic control. Methods: The MTT was performed at baseline and after 3 months in insulin treated diabetes patients using the modulation device vs. a control group without device. The dose used for the MTT was individually calculated based on the prandial insulin records from the patient diaries before the test. Blood was drawn for determination of glucose, insulin, C-peptide, proinsulin, triglycerides, free fatty acids, nitrotyrosine, and asymmetric dimethyl-arginine (ADMA) at multiple time-points from 0 to 300 min. A total of 32 patients from one site were included into this MTT study (8 female, 7 type 1 diabetes, age: 49.9 ± 12.5 yrs, HbA1c: 7.2 ± 0.5%). Results: During the BARMER study, mean HbA1c was treated to target (<6.5%) in both groups. The prandial insulin dose decreased in the MTT modulation device group by −17.1%, but remained unchanged in the control group (−0.1%, p < 0.001). No change was seen for the basal insulin dose in both treatment arms. There were no differences between the groups with respect to the postprandial curves for glucose, C-peptide, intact proinsulin, free fatty acids, and triglycerides. Insulin absorption was faster with the modulation device (Tmax: 60 ± 28 min vs. 99 ± 46 min, p < 0.05). Key limitations are the small patient sample size and impossibility to determine the short-term effects of device use. Conclusions: The results of this meal tolerance sub-study confirm that the observed prandial insulin dose reduction when using the injection site modulation device has no negative impact on postprandial metabolism.